Physics-based search and optimization: Inspirations from nature - Siddique, Nazmul; Adeli, Hojjat (Expert systems, 2016)
This paper presents a review of recently developed physics‐based search and optimization algorithms that have been inspired by natural phenomena. They include Big Bang–Big Crunch, black hole search, galaxy‐based search, artificial physics optimization, electromagnetism optimization, charged system search, colliding bodies optimization, and particle collision algorithm.